The Relationship between the Principal’s Leadership Behavior and the Intensity of Academic Supervision Implementation with Teacher Performance - Marhawati, Besse; Masaong, Abd. Kadim; Lestari, Dian (Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
This lack of teacher competence can impact teacher performance. The possible factors can affect teacher performance, namely, the leadership behaviors of the school principal and the intensity of the implementation of academic supervision. This study aims to analyze the relationship between principal leadership behaviors and the intensity of the implementation of academic supervision with teacher performance. This study uses a quantitative with a correlational design—data collection techniques using a questionnaire (questionnaire), observation, and documentation. Data analysis used a data validity test, reliability test, data normality test, data linear test, significance test, and hypothesis test by calculating the correlation coefficient. The results show (1) the principal's leadership behaviors has a positive and significant relationship with teacher performance, namely 50.2%, (2) the intensity of the implementation of academic supervision has a positive and significant relationship with teacher performance, namely 22.2%, (3) the principal's leadership behaviors and the intensity of the implementation of academic supervision has a positive and significant relationship with teacher performance, namely 71.07%.